Temporary Devider as an innovation tool in reducing operational losses of PT PLN (Persero) UP3 Sidoarjo - Zaputra, Gaggah; Ayuni, Shazana Dhiya; Anshory, Izza; Falah, Agus Hayatal (Universitas Nurul Jadid, 2025)
Temporary Devider is a new tool that was created in October 2024 by the PT PLN (PERSERO) UP3 SIDOARJO PDKB Team. Temporary Devider was created to help and solve problems with SUTM maintenance work that could not be carried out by the PDKB team due to high risk factors. The results of the study from 5 implementations in the PT PLN (Persero) UP3 Sidoarjo work area, local blackouts by utilizing the Temporary Devider as a new innovation tool with an investment value IDR 4,000,000 can reduce the difference in company losses by 89,376.08 kWh or Rp. 104,263,090 when compared to blacking out one feeder and 16,839.02 kWh or IDR 19,578,227 when compared to per-section outages. The use of Temporary Deviders has been proven to be able to reduce losses due to blackouts which result in Energy Not Supplied.